1959
DOI: 10.1017/s0009840x00173123
|View full text |Cite
|
Sign up to set email alerts
|

The Hoopoe's Song

Abstract: THE CLASSICAL REVIEW 199 : best candidate. We have been influenced by Thucydides' selection, emphasis, and portrayal of the events of 425; so had the Hellenistic scholars; Aristophanes had not. i (ii) If the slave is Nicias, he is not necessarily invested with the character ; which the Sicilian Expedition, several years after Eq., revealed in Nicias. (iii) In the whole of the opening dialogue of Eq. there is no passage which '• requires for the appreciation of its humour any knowledge of the character of any r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These differences stem primarily from the nature of the macrocyclic ring. Cyclen adopts a square conformation, defined by Dale’s nomenclature as [3,3,3,3], in which the nitrogen atoms are located on the sides of the ring and each ethylene bridge adopts a gauche conformation. It has been observed that if the conformation of cyclen is distorted into a another conformation significant loss of chelate stability can sometimes result . In the case of pyclen, however, the rigidity of the pyridine group dictates that one side of the macrocycle must incorporate 4 bonds and so a [3,3,3,3] conformation is impossible.…”
Section: Resultsmentioning
confidence: 99%
“…These differences stem primarily from the nature of the macrocyclic ring. Cyclen adopts a square conformation, defined by Dale’s nomenclature as [3,3,3,3], in which the nitrogen atoms are located on the sides of the ring and each ethylene bridge adopts a gauche conformation. It has been observed that if the conformation of cyclen is distorted into a another conformation significant loss of chelate stability can sometimes result . In the case of pyclen, however, the rigidity of the pyridine group dictates that one side of the macrocycle must incorporate 4 bonds and so a [3,3,3,3] conformation is impossible.…”
Section: Resultsmentioning
confidence: 99%
“…In the early days of conformational analysis, only symmetrical conformations of the medium-ring-cycloalkanes and derivatives were thought to be local minima or even TSs for conformational interconversion, 34 but this proved not to be the case. 35,36 Nowadays, it is well known that energy minima have to be carefully distinguished from TSs in the PEHS. Extensive searches of the conformational energy hypersurface for local minima should include the barriers separating pairs of conformations.…”
Section: Introductionmentioning
confidence: 99%